Protein partitioning of pregnant and lactating rabbit does fed combination of concentrates and stylosanthes hamata hay - Latu, M. Y.; Tsavkar, D.T.; Olutunmogun, A. K.; Barje, P. P.; Iyeghe-Erakpotobor, G. T. (Nigerian Journal of Animal Science, 2023)
The study evaluate protein partitioning of pregnant and lactating rabbit does offered levels of concentrate and Stylosanthes hamata hay to ascertain whether it meets their high reproductive and nutritional requirements. Forty-eight nulliparous crossbred does (New Zealand White x California and California x Chinchilla breeds) of eight months of age were allocated to four dietary treatments in a completely randomised design. During pregnancy, 150 g/doe/day concentrate and Stylosanthes hamata hay combinations (30:120g, 60:90g, 90:60g and 120:30g) of feed was offered while 350 g/doe/day concentrate and Stylosanthes hamata hay combinations (70:280g, 140:210g, 210:140g and 280:70g) was offered during lactation. Data collected for live weight (LW), digestible crude protein DCPintake and litter weight were used to estimate metabolic weight, protein requirement for maintenance, foetal growth and lactation of rabbit does. Results showed that pregnant rabbit does fed the combinations had significant (P<0.05) differences in the parameters considered. The 4th week had significant (P<0.05) difference over the 2nd week in most parameters except LW (2570 to 2640) and DCPmaintenance (7.50 to 7.64g/day) that had no significant (P>0.05) differences. During lactation, all parameters showed no significant (P>0.05) difference. Therefore, the diet combinations were adequate to satisfy protein requirement of pregnant does but inadequate for lactating does.